The Potential Role of Preoperative Posterior Cerebral Artery Involvement in Predicting Postoperative Transient Neurological Deficits and Ischemic Stroke After Indirect Revascularization in Patients With Moyamoya Disease - Araki, Yoshio; Yokoyama, Kinya; Uda, Kenji; Kanamori, Fumiaki; Takayanagi, Kai; Ishii, Kazuki; Nishihori, Masahiro; Goto, Shunsaku; Tsukada, Tetsuya; Takeuchi, Kazuhito; Tanahashi, Kuniaki; Nagata, Yuichi; et al. (World neurosurgery, 2024)
Transient neurological deficits (TNDs) are known to develop after direct bypass for Moyamoya disease and may be risk factors for subsequent stroke. However, the factors involved in the development of TNDs and stroke after indirect revascularization alone, including their association with subsequent stroke, remain unclear. The purpose of this study was to investigate this issue. The subjects of the study were 30 patients with Moyamoya disease who underwent a total of 40 indirect revascularization procedures at our institution. Clinical and radiological data were collected retrospectively. To examine factors associated with the development of postoperative TND/stroke/asymptomatic disease, the clinical characteristics of each group were statistically compared. The mean age at surgery was 7 years (range 1–63). TNDs developed after surgery in 9 out of 40 patients (22.5%). Stroke in the acute postoperative period occurred in 3 patients (7.5%), all of whom experienced cerebral infarctions. Demographic data and preoperative clinical information were not different between the groups. However, posterior cerebral artery involvement on preoperative imaging was significantly associated with the development of TNDs and stroke (P = 0.006). Furthermore, postoperative stroke was associated with unfavorable outcomes (P = 0.025). Posterior cerebral artery involvement is significantly associated with the occurrence of TNDs. In contrast, TNDs after indirect revascularization have little relationship with the subsequent development of stroke. TNDs usually resolve without new strokes, and a better understanding of this particular pathology could help establish an optimal treatment regimen.